Prevalence of ideal cardiovascular health and its relationship with relative handgrip strength in rural northeast China - Shao, Jingan; Yao, Bin; Yu, Zhecong; Xu, Jiahui; Wu, Jing; Ma, Yanan; Zheng, Liqiang; Sun, Zhaoqing (Frontiers in Cardiovascular Medicine, 2023)
Abstract Objectives: We aimed to investigate the ideal cardiovascular health (CVH) and the relationship between handgrip strength and ideal CVH and its components in rural China. Methods: A cross-sectional study was performed among 3203 rural Chinese individuals aged ≥35 years in the Liaoning Province of China. Of these, 2,088 participants completed the follow-up survey. Handgrip strength was estimated using a handheld dynamometer and normalized to body mass. Ideal CVH was measured using seven health indicators (smoking, body mass index, physical activity, diet, cholesterol, blood pressure, and glucose). Binary logistic regression analyses were performed to assess the correlation between handgrip strength and ideal CVH. Results: The ideal CVH rate was higher in women than in men (15.7% vs. 6.8%, P<0.001). A higher handgrip strength was correlated with a higher proportion of ideal CVH (P for trend <0.001). After adjusting for confounding factors, the odds ratios (95% confidence interval) of ideal CVH across increasing handgrip strength tripartite were 1.00 (reference), 2.368 (1.773, 3.164), and 3.642 (2.605, 5.093) in the cross-sectional study and 1.00 (reference), 2.088 (1.074, 4.060), and 3.804 (1.829, 7.913) in the follow-up study (P for all <0.05). Conclusion: In rural China, ideal CVH rate was low, and handgrip strength was positively correlated with ideal CVH. Grip strength can be a rough predictor of ideal CVH and can provide guidelines for improving CVH in rural China.